Pemahaman Aspek Estetik dan Eferen Wacana Kopi serta Dampaknya terhadap Prosedur Eksplorasi Calon Guru Bahasa Indonesia di Universitas Jember - Rusdhianti Wuryaningrum (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2020)
This study aims to describe the mastery of aesthetic and efferent aspects in understanding coffee discourse and its impact on the ability of exploratory procedures for prospective Indonesian language teacher students. The study was applied to 14 students who practice teaching or KK-PLP II at SMK Negeri 2 and SMK 4 Jember. The research method is applied qualitatively and quantitatively. The results of qualitative analysis show mastery of aesthetic aspects consisting of culture and experience of research subjects on planting to serving coffee and efferent aspects about factual, informational, and conceptual knowledge about planting to serving coffee. The results of quantitative analysis were obtained by 1) normality test data on the ability of aesthetic aspects, efferent, and the ability of exploratory procedures; (2) multiple linear regression test; (3) the significance of the regression coefficient test to show the significant impact of understanding aesthetic and efferent aspects on the ability of exploratory procedures. From the multiple linear regression test, it is known that the understanding of the aesthetic aspect (X1) is 0.001 or ,00.05 and the understanding of the efferent aspect is 0.012 or ≤0.05. Thus, understanding the aesthetic and efferent aspects significantly impacts the ability of exploratory procedures in the learning process.